(3GdJZjQGJ GdJj dMbJ SjGOI GdOhdI aj Xd JfGei GdJLGQI GdOhdjI (B/ s - (3GdSjO YHOGdefYe GdeQGcHjs; (3jMji GdLed (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2004)
(3HOCJ GdQSGdI HebOeI JegO ddONhd aj ehVhYgG GdeJYdb HSjGOI GdOhdI hGdJLGQI GdOhdjI hGdJj JfGhdJg aj GdbSejf(B: (3GdbSe GdChd, SjGOI GdOhdI hGdJLGQI GdOhdjI Hjf Gdeaghejf GdJbdjOj hGdMOjK, aj HGHjf , Ke GdbSe GdKGfj, hjJfGhd SjGOI GdOhdI hGdJLGQI GdOhdjI hefXeGJgG fXQI eYGUQI(B"(3, aj HGHjf JfGhd GdHGH GdChd SjGOI GdOhdI hGdJLGQI GdOhdjI , hGdHGH GdKGfj GdJLGQI GdOhdjI hSjGOI GdOhd GdfGejI GdOhd GdYQHjI cfehPL(B" (3hHjfJ GdQSGdI Cf eUWdM GdSjGOI jQJHW ef MjK GdhLhO HfTCI hJWhQ GdOhdI, hQUOJ GdJZjQGJ GdJj dMbJ gPG GdeUWdM aj VhA GdJHGOd GdJLGQj ZjQ GdeJcGaF Hjf GdOhd GdeJbOeI hGdfGejI, ehVMI Cf ShA GdEOGQI GdGbJUGOjI hGdaSGO GdSjGSj hGdGbJUGOj gh GdPj jDOj Edi VYa GdOhd GdfGejI, eeG jDOi Edi JONd GdOhd GdcHQi aj TFhfgG , hHGdJGdj jfJbU ef SjGOJgG hjHbjgG aj ESGQ GdJHYjI hGdJNda hGdJj dG acGc dgG efgeG EdG HGdJfejI hGdOjebQGWjI eYG(B.s
2004. (3CWQhMI (B((3OcJhQGg(B)-s
(3HHdjhLQGajG(B: (3UaMGJ (B448-470.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3fXQjI GdSjGOIs; (3GdJLGQI GdOhdjIs; (3efXeGJ GdJLGQI GdOhdjIs; (3GdbGfhf GdOhdj GdYGes; (3UfOhb GdfbO GdOhdjs; (3GdHfc GdOhdj ddEfTGA hGdJYejQs; (3GdOhd GdfGejIs; (3fXQjI GdSjGOIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2004